Unification of documents in pre-revolutionary Russia: historical and legal issues - O. V. Marchenko (Правоприменение, 2021)
The subject. The article reveals the main historical trends and legal problems concerning unification of documents used by Russian authorities during different historical periods. The purpose of the article is to identify the prerequisites for the origin of document unification, as well as to characterize the periods of development and main directions of document flow standardization in pre-revolutionary Russia. The methodology includes historical-legal method, formal-legal method, systematic approach, chronological method, analysis, synthesis. The main results of research. Scientific understanding of the historical and legal aspects of document flow standardization is closely related to the main stages of its development, and therefore the problem of periodization of document flow standardization in Russia for the purpose of systematization and scientific generalization of this field of knowledge comes to the fore. The chronological approach was chosen as the most appropriate criterion, which allows to trace the evolutionary development of document management standardization, link it with the general history of office work in Russia and state policy in this area. The research will help to determine ways to improve the current system of document management standardization in Russia. The research topic becomes especially relevant in connection with the activation of the processes of implementation of international standards, and the wide application of foreign practice in the field of documentation management over the past decade in Russia. Generalization and analysis of the historical experience of our country in this area makes it possible to identify the national specifics of document management and its standardization. It helps to determine the prospects for the implementation of international standards. Conclusions. The study of the history of documentation practice in Russia allows us to conclude that the issues of document flow rationalization were of great importance since the XVII century. Considerable experience was accumulated in the field of document unification in pre-revolutionary Russia. The beginnings of document unification arose at the dawn of the XVII century and developed gradually with the formation and complexity of the office system in Russia. At the first stage unification was manifested in the consolidation of spontaneously formed norms and rules for drawing up business papers, by the end of the XIX century it turned into an independent element in the field of document management. The gradual evolution of the form as well as the introduction of stamp paper led to the appearance of legally established forms of documents with permanent details in the XIX century, and the first unified documentation systems were created. The appearance of collections of business paper samples showed that government and Russian society understood the importance of using sustainable document models in order to streamline document flow.